The Impact of Negative Interest Rates (Negative Interest Gates ) on Guarantee And Liquidity Models In Clearing Houses L - Gea, Feman Jaya; Sianturi, Firman; Sinaga, Jannes; Sagala, Teguh; Siallagan, Hamonangan (Jurnal Ilmu Sosial dan Humaniora, 2025)
The Negative Interest Rate Policy (NIRP) is an unconventional monetary tool adopted by several central banks in response to deflationary pressures and economic slowdown. This study aims to analyze the impact of negative interest rates on collateral models and liquidity conditions within clearing institutions (central counterparties/CCPs). The research employs a descriptive qualitative approach through literature review, using secondary data from academic journals, BIS, IMF, and ECB reports, as well as regulatory documents related to risk management in clearing institutions. The findings indicate that negative interest rates increase demand for high-quality liquid assets (HQLA), tighten the availability of eligible collateral, and prompt CCPs to raise margin requirements and haircut levels. Furthermore, negative interest rates place liquidity pressures on financial institutions due to reduced banking profitability and increased variation margin needs during periods of heightened volatility. These dynamics heighten systemic risk if not accompanied by adequate mitigation frameworks. This study highlights the importance of strengthening liquidity structures, diversifying collateral assets, and ensuring access to central bank liquidity facilities to maintain clearinghouse stability under negative interest rate environments